ANALISIS PROGRAM PENANGGULANGAN KRISIS KESEHATAN AKIBAT BENCANA DI PROVINSI RIAU TAHUN 2025 - Khair Anthony, Eko; Ismainar , Hetty; Anusirwan (LPPM Universitas Awal Bros, 2025)
Disaster-related health crisis management is a strategic component in maintaining the resilience and sustainability of regional health systems. This study aims to analyze the implementation of disaster-related health crisis management programs in Riau Province, Indonesia, in 2025 across the pre-crisis, emergency response, and post-crisis phases. A qualitative approach was employed, utilizing document analysis, field observations, and in-depth interviews with relevant stakeholders. The findings indicate that program implementation has not been optimal due to limitations in human resources, insufficient funding allocation, the absence of standardized operational documents such as Contingency Plans and cross-sectoral Standard Operating Procedures, as well as weaknesses in the healthcare logistics system. High-risk environmental conditions, including haze, flooding, and land fires, further complicate health emergency responses. A significant gap exists between national policy standards and local implementation capacity. This study emphasizes the need to strengthen human resource capacity, enhance funding, improve healthcare logistics, integrate early warning systems, and promote cross-sectoral collaboration and community empowerment to improve health system resilience in future disasters.